A copper foil composite current collector and a method for manufacturing the same
Patent Information
- Application Number
- CN202611065109.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-17
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]然而,高分子薄膜本身通常为绝缘材料,复合集流体上下两层铜层之间难以自然导通
[0038]通过在中间聚合物膜边缘区域设置填铜孔部形成导铜连接部,可在复合集流体厚度方向建立稳定导电通路,有利于实现上下铜层之间低电阻连接;
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery current collector technology, and in particular to a copper foil composite current collector for lithium batteries, sodium batteries and solid-state batteries and its preparation method. Background Technology
[0002] Current collectors are an important component of electrochemical batteries, primarily responsible for electron collection and transport, as well as supporting electrode active materials. For systems such as lithium-ion batteries, sodium-ion batteries, and solid-state batteries, the conductivity, mechanical stability, interfacial bonding performance, and lightweight level of the current collector directly affect the battery's energy density, rate performance, cycle life, and processing adaptability.
[0003] Currently, negative electrode current collectors typically use single-layer copper foil. However, as batteries develop towards higher energy density and lighter weight, traditional single-layer copper foil is prone to problems such as decreased tensile strength, insufficient bending resistance, and wrinkles, cracks, or even breakage during winding or stacking after thinning. To address these issues, a composite current collector structure using a polymer film as an intermediate support layer and copper layers formed on the upper and lower surfaces of the polymer film has become an important development direction.
[0004] However, polymer films are typically insulating materials, making it difficult for the upper and lower copper layers of a composite current collector to conduct naturally. Using subsequent welding, mechanical connections, or multi-point via structures in the main body often results in complex processes, localized stress concentrations, reduced effective coating area, or insufficient conductivity consistency. Therefore, achieving low-resistance, mass-producible conductive connections between the upper and lower copper layers while ensuring efficient utilization of the main body's effective area is a key technical problem that needs to be solved in this field. Summary of the Invention
[0005] The purpose of this invention is to provide a copper foil composite current collector and its preparation method. By setting a through hole in the edge region of the intermediate polymer film and forming a copper connection part in the through hole that is electrically in contact with the upper and lower copper layers, stable conduction between the upper and lower copper layers along the thickness direction is achieved, while taking into account the requirements of lightweight, mechanical strength and continuous manufacturing.
[0006] To achieve the above objectives, the present invention adopts the following technical solution:
[0007] A copper foil composite current collector includes, from top to bottom, an upper copper layer, an upper adhesive layer, an intermediate polymer film layer, a lower adhesive layer, and a lower copper layer. The intermediate polymer film layer has at least one hole extending through its thickness direction in its edge region. The hole is filled with copper to form a copper conductive connection. The copper conductive connection extends along the thickness direction of the intermediate polymer film layer, with its upper end in electrical contact with the upper copper layer and its lower end in electrical contact with the lower copper layer, thus forming a conductive path along the thickness direction between the upper and lower copper layers.
[0008] Preferably, the thicknesses of the upper copper layer and the lower copper layer are 0.8-2.0 μm, respectively.
[0009] Preferably, the dry film thicknesses of the upper adhesive layer and the lower adhesive layer are 0.3-2.0 μm, respectively.
[0010] Preferably, the thickness of the intermediate polymer film layer is 2.0-5.0 μm.
[0011] Preferably, the pores are located in the single-sided edge region, double-sided edge region, corner region, or edge reserved conductive region of the intermediate polymer film layer.
[0012] Preferably, the planar shape of the hole is any one of a circle, an ellipse, a strip, a rectangle, or a polygon.
[0013] Preferably, the copper conductive connector is fitted to the inner wall of the hole and extends through the thickness of the intermediate polymer film layer.
[0014] Preferably, the two ends of the copper conductive connector reach or approach the upper and lower end faces of the hole, and form electrical contact with the upper copper layer and the lower copper layer respectively. The electrical contact can be direct contact or contact formed by composite compaction.
[0015] Preferably, the adhesive layer is formed by curing a maleic anhydride-grafted polyolefin adhesive.
[0016] Preferably, the intermediate polymer film layer is a polyethylene film, a polyethylene terephthalate film, a polypropylene film, a polyimide film, or other insulating polymer films.
[0017] Preferably, under certain preferred implementation conditions, the contact resistance between the upper and lower copper layers of the copper foil composite current collector, as measured according to the test conditions described in the performance test section of this specification, can be less than 2.1 mΩ, and more preferably less than 2.0 mΩ.
[0018] The present invention also provides a method for preparing the above-mentioned copper foil composite current collector, comprising the following steps:
[0019] The first copper layer and the second copper layer correspond to the upper copper layer and the lower copper layer in the final product, respectively, or to the lower copper layer and the upper copper layer, respectively.
[0020] (1) Base film pretreatment:
[0021] An intermediate polymer film is provided, and at least one hole penetrating the thickness direction is formed in the edge region of the intermediate polymer film; an adhesive is coated on the upper and lower surfaces of the intermediate polymer film respectively, and after drying, an upper adhesive layer and a lower adhesive layer are formed to obtain a pretreated base film.
[0022] (2) First copper layer composite:
[0023] A first copper layer is formed on the surface of the cathode roller by aqueous electroplating. The adhesive layer on one side of the pretreated base film is hot-pressed together with the first copper layer and then peeled off from the cathode roller after cooling to obtain a single-sided composite.
[0024] (3) Fill the hole with copper:
[0025] A temporary protective layer is provided on the outer surface of the first copper layer formed in the single-sided composite to reduce unintended deposition in non-hole areas; preferably, a deposition exposure window is retained in the corresponding area of the hole, or the corresponding area of the hole is positioned as a priority deposition location; if necessary, the hole wall and orifice area are cleaned, activated, roughened, or plasma treated; then, using the first copper layer as the conductive base for electrodeposition, copper is gradually deposited and grown from the end of the hole that contacts the first copper layer into the hole through electroplating, forming a copper conductive connection extending along the thickness direction of the intermediate polymer film layer. One end of the copper conductive connection forms a stable electrical contact with the first copper layer, and the other end reaches or approaches the opening at the other end of the hole so as to form an electrical contact with the second copper layer during subsequent second copper layer composite;
[0026] (4) Second copper layer composite:
[0027] A second copper layer is formed on the surface of the cathode roller by water-based electroplating. The adhesive layer on the other side of the single-sided composite is hot-pressed to the second copper layer to make the copper conductive connection part make electrical contact with the second copper layer. After cooling, it is peeled off from the cathode roller to obtain a double-sided copper layer composite structure.
[0028] (5) Post-processing:
[0029] After removing the temporary protective layer, the copper foil composite current collector is obtained after cleaning and drying.
[0030] Preferably, the hole is formed by mechanical punching, laser drilling, die cutting, or a combination thereof.
[0031] Preferably, the current density of the aqueous electroplating is 5-20 A / dm². 2 The temperature of the electroplating solution is 15-30℃.
[0032] Preferably, the electroplating solution is a copper sulfate-sulfuric acid system electroplating solution, wherein the concentration of copper sulfate is 150-250 g / L and the concentration of sulfuric acid is 40-80 g / L.
[0033] Preferably, the hot-pressing composite temperature is 60-140℃ and the pressure is 0.5-2.0MPa.
[0034] Preferably, the temporary protective layer is an acid-resistant and removable polymer protective layer, and more preferably an epoxy resin system protective layer, a polyimide system protective layer, or other peelable protective layer that can be alkali-removed after formulation design.
[0035] Preferably, the post-treatment employs a removal process that matches the temporary protective layer system to remove the temporary protective layer; for alkali-removable protective layers, alkaline treatment is preferred, wherein the alkaline solution is preferably a 0.5-2 mol / L NaOH solution, the treatment temperature is 20-60℃, and the treatment time is 10-60 min.
[0036] The present invention also provides the application of the above-mentioned copper foil composite current collector in lithium batteries, sodium batteries or solid-state batteries.
[0037] Compared with the prior art, the present invention has at least the following beneficial effects:
[0038] By setting copper-filled holes in the edge region of the intermediate polymer film to form a copper-conducting connection, a stable conductive path can be established in the thickness direction of the composite current collector, which is beneficial to achieving low-resistance connection between the upper and lower copper layers.
[0039] The conductive structure is located in the edge area, which can reduce the impact on the coating area of the main active material;
[0040] The use of a polymer film-copper layer composite structure not only achieves lightweighting but also improves the overall flexibility and bending stability of the current collector.
[0041] The process involves drilling, coating, water-based electroplating, hot-pressing lamination, and protective layer removal, which provides a basis for continuous preparation and facilitates industrial implementation.
[0042] Under preferred implementation conditions, the resulting copper foil composite current collector can achieve a balance of low contact resistance, good interlayer bonding performance, and good bending durability. Detailed Implementation
[0043] The present invention will be further described below with reference to embodiments. It should be understood that these embodiments are only for explaining the present invention and are not intended to limit the scope of protection of the present invention. Conventional modifications, equivalent substitutions, and process optimizations made by those skilled in the art without departing from the concept of the present invention should all be considered to fall within the scope of protection of the present invention.
[0044] I. Material and Process Requirements
[0045] Intermediate polymer film layer:
[0046] The intermediate polymer film layer can be made of insulating polymer films such as polyethylene (PE) film, polyethylene terephthalate (PET) film, polypropylene (PP) film, and polyimide (PI) film; considering the lightweight, processability and interlayer composite effect, the thickness is preferably 2.0-5.0μm.
[0047] Adhesive layer:
[0048] The binder is preferably a maleic anhydride-grafted polyolefin binder; its function is to enhance the interfacial bonding between the intermediate polymer film layer and the copper layer. The binder can be applied to the surface of the intermediate polymer film layer by means of roller coating, slot coating, or blade coating, and after drying, an binder layer with a thickness of 0.3-2.0 μm is formed.
[0049] Copper layer:
[0050] The upper and lower copper layers are preferably formed on the surface of the cathode roller using an aqueous electroplating method, and then hot-pressed together with the intermediate polymer film layer; the copper layer thickness is preferably 0.8-2.0 μm. The electroplated copper layer preferably has a continuous, dense surface condition, free from obvious pinholes, scorching, and large-area pitting.
[0051] Edge holes and copper conductor connections:
[0052] Holes are located at the edge of the intermediate polymer film layer to form a thickness-direction conductive connection between the upper and lower copper layers. The number of holes can be one, two, four, or more; they can be located on one side edge, both sides edge, corner area, or specific pre-reserved conductive area. The hole diameter is preferably 15-2000 μm, and the spacing between adjacent holes can be adjusted according to the product width, slitting edge design, current distribution requirements, and subsequent cell assembly method.
[0053] A copper conductive connection is formed within the hole by electrodeposition. Preferably, the copper conductive connection extends substantially through the hole along the thickness direction of the intermediate polymer film layer, and establishes electrical contact with the first and second copper layers at both ends. Preferably, one end of the copper conductive connection forms direct electrical contact with the first copper layer immediately after the hole-filling electroplating, while the other end forms direct contact or is press-fitted to the second copper layer during the subsequent second copper layer lamination process.
[0054] In some embodiments, the adhesive layer in the region adjacent to the hole may form a thinner, discontinuous, or partially incompletely covered area near the hole opening due to the characteristics of the opening, coating coverage, hole retraction, thermal pressure flow, or local avoidance, in order to facilitate electrical contact between the end of the copper conductive connector and the corresponding copper layer. In other words, the adhesive layer is preferably continuously distributed in the main body area to ensure interlayer bonding, while in the corresponding conductive area of the hole, its local morphology can be adapted to the needs of conductive connection formation, without being limited to completely blocking metal contact.
[0055] In a preferred embodiment, the upper and / or lower ends of the copper conductive connector may be substantially flush, nearly flush, or slightly protruding relative to the end face of the hole, thereby forming a stable electrical contact through local contact, local compaction, or local interlocking during the subsequent hot-pressing of the second copper layer. The slight protrusion is preferably controlled within a range that does not significantly damage the composite flatness or cause obvious stress concentration.
[0056] Temporary protective layer:
[0057] To prevent unintended deposition, corrosion, or contamination of the copper layer already formed during the copper filling process, a temporary protective layer can be applied to the outer surface of the copper layer. The temporary protective layer should possess the following characteristics:
[0058] It is resistant to electroplating solution environments;
[0059] It can be effectively removed under post-treatment conditions;
[0060] It does not significantly damage the surface of the already formed copper layer.
[0061] A temporary protective layer is preferably made of a peelable protective resin system. For epoxy or polyimide systems, the formulation should be designed to suit the subsequent removal conditions.
[0062] II. Preparation Method
[0063] Step S1: Opening pores in the base film and applying adhesive
[0064] Take an intermediate polymer film and form at least one hole extending through the thickness direction in its edge region. After creating the hole, clean the edges of the hole and the film surface.
[0065] Subsequently, an adhesive is uniformly coated onto both the upper and lower surfaces of the intermediate polymer film. Preferably, the coating amount is adjusted by online thickness monitoring to ensure that the thickness of the upper and lower adhesive layers after drying is controlled between 0.3 and 2.0 μm, respectively. After coating, the film is heated and dried to allow the solvent to evaporate and form a stable adhesive layer.
[0066] Step S2: Formation and composite of the first copper layer
[0067] A first copper layer is deposited on the surface of the rotating cathode roller using a copper sulfate-sulfuric acid electroplating solution. Preferred conditions are: copper sulfate 150-250 g / L, sulfuric acid 40-80 g / L, electroplating solution temperature 15-30℃, and current density 5-20 A / dm³. 2 .
[0068] The adhesive layer on one side of the pretreated intermediate polymer film is bonded to the first copper layer on the surface of the cathode roller, and then composited using a hot press roller. The preferred hot pressing temperature is 60-140℃, and the preferred pressure is 0.5-2.0MPa. After cooling, the composite is peeled off to obtain a single-sided composite.
[0069] Step S3: Fill the hole with copper
[0070] A temporary protective layer is formed on the outer surface of the first copper layer of the single-sided composite to reduce unwanted copper deposition in non-hole areas during the through-hole plating process and to minimize contamination or adverse effects of the plating solution on the surface of the formed copper layer. The temporary protective layer is preferably formed by roller coating, slot coating, gravure coating, or spraying. The protective layer material is preferably an acid-resistant and removable polymer protective layer, more preferably an alkali-removable epoxy resin system, a removable polyimide system, or other temporary protective materials formulated for subsequent removal. The dry film thickness of the temporary protective layer is preferably 5-15 μm, more preferably 8-12 μm.
[0071] In a preferred embodiment, to ensure effective electrodeposition in the area corresponding to the hole, the temporary protective layer covers most of the exposed surface of the first copper layer, while retaining an exposure window required for deposition in the area corresponding to the hole. Alternatively, in subsequent positioning processes, the area corresponding to the hole can be placed in a deposition region with more favorable electric field and ion transport, thereby allowing copper to preferentially deposit and grow within the hole. The exposure window can be formed through selective coating, reserving uncoated areas, local windowing, laser removal, mechanical removal, or other methods that expose the deposition area corresponding to the hole.
[0072] Before through-hole electroplating, the inner wall and orifice area of the holes can be pretreated as needed. Pretreatment preferably includes one or more of the following: surface cleaning, dust removal, degreasing, activation, roughening, and plasma treatment, to improve the cleanliness, surface energy, and copper deposition adhesion of the hole wall surface. For polymer films with strong surface inertness, such as polyethylene and polypropylene, corona treatment, plasma treatment, chemical roughening, or a combination thereof are preferred to improve the adaptability of the orifice and adjacent areas to subsequent copper deposition.
[0073] The single-sided composite material with a temporary protective layer is positioned so that the hole is located at the hole-filling electroplating station, and the first copper layer serves as the conductive base for electrodeposition, connected to the electroplating circuit. During electroplating, copper ions preferentially precipitate in the hole region connected to the first copper layer under the action of an external electric field. Copper deposition begins at the end of the hole that contacts the first copper layer and gradually grows towards the other end along the thickness direction of the hole, thereby forming a continuous copper-conducting connection within the hole. Preferably, the copper-conducting connection is substantially continuous within the hole along the thickness direction of the intermediate polymer film layer, and its thickness dimension is preferably substantially equivalent to the hole depth, so that one end forms a stable electrical contact with the first copper layer, and the other end reaches or approaches the opening at the other end of the hole, so as to form an electrical contact with the second copper layer during subsequent lamination.
[0074] Preferably, the end of the copper conductive connector is substantially flush with or nearly flush with the upper and lower end faces of the hole. In some embodiments, the end of the copper conductive connector may protrude slightly relative to the end face of the hole, but the protrusion height is preferably controlled within a range that does not significantly affect the flatness of the subsequent second copper layer and the continuity of the adhesive layer. Insufficient filling may result in the copper conductive connector having difficulty forming a stable electrical contact with the second copper layer; excessive filling may result in localized protrusions, stress concentration, or uneven composite. Therefore, it is preferable to control the amount of plating used to fill the hole so that the copper conductive connector can balance conductivity reliability and subsequent composite adaptability.
[0075] The via-filling electroplating preferably employs an aqueous copper electroplating system that is the same as or compatible with the copper layer formation process, such as a copper sulfate-sulfuric acid electroplating solution. Under preferred conditions, the copper sulfate concentration is 150-250 g / L, the sulfuric acid concentration is 40-80 g / L, the electroplating solution temperature is 15-30°C, and the current density is 5-20 A / dm³. 2 To improve the uniformity and filling integrity of copper deposition within the holes, one or more control methods can be used, such as constant current electroplating, segmented current electroplating, pulse electroplating, and pulse reverse electroplating. Alternatively, electroplating solution circulation, cathode movement, local flow guidance at the work station, or stirring can be combined to improve mass transfer conditions near the holes.
[0076] In a preferred embodiment, by controlling the window opening range of the protective layer, the current density, the electroplating time, and the deposition method, copper deposition is mainly concentrated in the area corresponding to the hole, while reducing the thickness increase of other exposed areas of the first copper layer. If necessary, the surface morphology of the copper conductive connection can be inspected after the hole-filling electroplating to confirm its continuity, positional integrity, and connection status with the first copper layer. After hole-filling electroplating, a single-sided composite with copper conductive connections is obtained.
[0077] Step S4: Formation and composite of the second copper layer
[0078] A second copper layer, preferably 0.8-2.0 μm thick, is deposited on the surface of another cathode roller. The adhesive layer on the other side of the single-sided composite with the copper conductive connector is then hot-pressed to the second copper layer. During the bonding process, the end of the copper conductive connector in the corresponding area of the hole contacts the second copper layer, and a stable electrical contact can be formed under the hot-pressing pressure through local compaction, local fitting, or local extrusion of the adhesive layer adjacent to the hole, thereby creating a continuous conductive path between the first copper layer, the copper conductive connector, and the second copper layer. After cooling and peeling, a double-sided copper layer composite structure is obtained.
[0079] Step S5: Protective layer removal and post-processing
[0080] The temporary protective layer is removed using a removal process compatible with the temporary protective layer system. For alkaline-peelable protective layers, a 0.5-2 mol / L NaOH solution is preferred for treatment, with a preferred treatment temperature of 20-60℃ and a preferred treatment time of 10-60 min. To minimize adverse effects on the ultrathin copper layer and interlayer interfaces, the removal conditions are preferably controlled to ensure effective peeling of the protective layer while avoiding prolonged strong alkaline treatment that could cause surface deterioration, edge warping, or interface damage to the copper layer. After removal, the copper foil composite current collector is preferably thoroughly rinsed with deionized water until neutral, followed by low-tension conveying and gentle drying to obtain the final product.
[0081] Example 1:
[0082] This embodiment prepares a copper foil composite current collector with a polyethylene film as the intermediate polymer film layer.
[0083] Base film pretreatment:
[0084] A 3.0 μm thick polyethylene film is selected, and through holes are formed near the corners on both sides of its edges. The holes are circular with a diameter of 200 μm, and two holes are provided on each side. The holes are created using mechanical punching, and after punching, clean air and dust removal rollers are used to clean the film surface and the edges of the holes.
[0085] A micro-grooved roller coating method was used to uniformly coat maleic anhydride-grafted polyolefin adhesive on both the upper and lower surfaces of a polyethylene film. The solid content of the adhesive solution was 25 wt%, and the coating amount was controlled so that the thickness of the upper and lower adhesive layers was 1.5 μm after drying. The coated film was placed in an 80℃ oven for 20 min to dry, cooled, and then wound up. It was then allowed to stand at room temperature for 12 h to allow the adhesive layer to stabilize, resulting in a pretreated base film.
[0086] First copper layer composite:
[0087] The first copper layer was deposited on the surface of the cathode roller using a copper sulfate-sulfuric acid electroplating solution. The concentration of copper sulfate in the electroplating solution was 200 g / L, the concentration of sulfuric acid was 60 g / L, the temperature was 25℃, and the current density was 10 A / dm³. 2 The deposition time was controlled to achieve a first copper layer thickness of 1.5 μm.
[0088] The adhesive layer of the pretreated base film is bonded to the first copper layer on the surface of the cathode roller, and then laminated by a hot press roller at a temperature of 80°C, a pressure of 1.0 MPa, and a pressing time of 5 seconds. After cooling and peeling, a single-sided composite is obtained.
[0089] Copper filling of holes:
[0090] A layer of alkali-removable epoxy resin protective layer is roll-coated onto the outer surface of the first copper layer of the single-sided composite, with a dry film thickness controlled at 10 μm. After drying and curing at 80-120℃, a temporary protective layer is formed. Preferably, a local exposure window is reserved in the corresponding area of the hole, or the corresponding area of the hole is placed in the priority deposition area during subsequent positioning to reduce significant overplating in non-hole areas.
[0091] Before filling the holes with electroplating, the area near the hole opening and the hole wall is cleaned of dust. If necessary, further plasma treatment or corona treatment is used to improve the surface energy of the polyethylene hole wall surface and the adhesion of subsequent copper deposition.
[0092] The single-sided composite is positioned so that the first copper layer is connected to the electroplating circuit, and the hole is located at the hole-filling electroplating station. A copper sulfate-sulfuric acid electroplating solution with the same system as that used during the formation of the first copper layer is employed at 25°C and 10 A / dm³. 2 Under certain conditions, through-hole electroplating is performed, allowing copper to gradually deposit and grow from the end of the hole that contacts the first copper layer into the hole, forming a copper-conducting connector extending along the thickness direction of the polyethylene film. Preferably, the thickness dimension of the copper-conducting connector is substantially equivalent to the depth of the hole, ensuring that one end forms a stable electrical contact with the first copper layer, and the other end reaches or nearly reaches the opening at the other end of the hole, facilitating electrical contact with the second copper layer during subsequent lamination. Preferably, the end of the copper-conducting connector is substantially flush with or nearly flush with the end face of the hole.
[0093] In this embodiment, the hole-filling electroplating time is preferably 10-120s, which can be adjusted according to the hole diameter, film thickness and target filling state; under the premise of ensuring stable conduction of the copper conductive connection, it is preferable to avoid excessive deposition that would cause obvious protrusion of the hole opening.
[0094] Second copper layer composite:
[0095] Using the same electroplating solution system and process parameters as in step 2, a second copper layer with a thickness of 1.5 μm is formed on the surface of the cathode roller. The lower adhesive layer of the intermediate composite after filling the holes is aligned and bonded to the second copper layer, and then hot-pressed at 80°C and 1.0 MPa for 5 s, followed by cooling and peeling to obtain a double-sided copper layer composite structure.
[0096] Post-processing:
[0097] The above-mentioned double-sided copper layer composite structure was immersed in 1.0 mol / L NaOH solution and treated at 40°C for 30 min to remove the temporary protective layer; then it was rinsed with deionized water until neutral and dried at 80°C for 15 min to obtain the finished copper foil composite current collector.
[0098] The resulting current collector structure is as follows: upper copper layer 1.5μm / upper adhesive layer 1.5μm / polyethylene film layer 3μm / lower adhesive layer 1.5μm / lower copper layer 1.5μm, with a total thickness of approximately 9μm.
[0099] Example 2:
[0100] This embodiment prepares a copper foil composite current collector with PET film as the intermediate polymer film layer.
[0101] Base film pretreatment:
[0102] A 4.0 μm thick PET film was selected, and through-holes were formed in its edge region. These through-holes were circular, with a diameter of 300 μm, and were located on opposite side edges. Maleic anhydride-grafted polyolefin adhesive was uniformly coated onto both the upper and lower surfaces of the PET film using a micro-grooved roller coating method, controlling the thickness of both adhesive layers to be 2.0 μm after drying. The film was dried at 100°C for 25 min, cooled, wound up, and allowed to stand at room temperature for 12 h.
[0103] First copper layer composite:
[0104] A copper sulfate-sulfuric acid electroplating solution was used to deposit a first copper layer with a thickness of 1.8 μm on the surface of the cathode roller. The electroplating solution temperature was 25℃, and the current density was 10 A / dm³. 2 The pretreated base film and the first copper layer were hot-pressed at 90°C and 1.2 MPa for 6 seconds, and then cooled and peeled off to obtain a single-sided composite.
[0105] Copper filling of holes:
[0106] A removable temporary protective layer is formed on the outer surface of the first copper layer, with a dry film thickness of approximately 12 μm. Preferably, a deposition exposure window is provided in the corresponding area of the hole, or the hole is positioned in a priority deposition area to reduce overplating in non-hole areas.
[0107] If necessary, perform surface cleaning, activation, roughening, or plasma treatment on the area adjacent to the orifice and orifice walls. After positioning the single-sided composite, connect the first copper layer to the electroplating circuit and plate it at 25°C and 10A / dm. 2 Under these conditions, through-hole electroplating is performed, allowing copper to gradually deposit and grow from the end of the hole that contacts the first copper layer into the hole, forming a copper-conducting connection extending along the thickness direction of the PET film within the hole. Preferably, the copper-conducting connection substantially penetrates the thickness direction of the hole and forms a stable electrical contact with the first copper layer, with its other end reaching or approaching the opening at the other end of the hole to facilitate electrical contact with the second copper layer during subsequent lamination.
[0108] Second copper layer composite:
[0109] A second copper layer with a thickness of 1.8 μm is formed on the surface of the cathode roller. The other side of the intermediate composite after filling the holes is hot-pressed with the second copper layer at 90°C and 1.2 MPa for 6 seconds, and then cooled and peeled off.
[0110] Post-processing:
[0111] The temporary protective layer is removed using an alkaline solution or a removal solution compatible with the protective layer system. It is then rinsed with deionized water until neutral and dried to obtain the finished copper foil composite current collector.
[0112] The resulting product structure is as follows: upper copper layer 1.8μm / upper adhesive layer 2μm / PET film layer 4μm / lower adhesive layer 2μm / lower copper layer 1.8μm, with a total thickness of approximately 11.6μm.
[0113] Example 3:
[0114] This embodiment illustrates the feasibility of preparing ultrathin copper foil composite current collectors under the condition of a relatively thin intermediate polymer film layer.
[0115] (1) Opening of base film and coating
[0116] A 2.0 μm thick polyethylene film was selected as the intermediate polymer film layer. A circular hole with a diameter of 100 μm was formed in one of the edge regions using laser drilling. After drilling, a dust-free airflow was used to remove dust from the film surface and the edges of the hole.
[0117] Subsequently, maleic anhydride-grafted polyolefin adhesive was coated on the upper and lower surfaces of the polyethylene film using a slot coating method. After drying at 80°C for 2 minutes, an upper adhesive layer and a lower adhesive layer with a thickness of approximately 1.0 μm were formed on both sides of the film, resulting in a pretreated base film.
[0118] (2) Formation and composite of the first copper layer
[0119] A copper layer was formed on the surface of a rotating cathode roller using a copper sulfate-sulfuric acid electroplating solution. The copper sulfate concentration was 180 g / L, the sulfuric acid concentration was 60 g / L, the electroplating solution temperature was controlled at 22°C, and the current density was controlled at 8 A / dm³. 2 A first copper layer with a thickness of approximately 1.0 μm is formed.
[0120] One side of the pretreated base film is bonded to the first copper layer on the surface of the cathode roller, and hot-pressed for 5 seconds at 80°C and 0.8MPa. After cooling, it is peeled off from the cathode roller to obtain a single-sided composite.
[0121] (3) Fill the hole with copper
[0122] A temporary protective layer is formed on the outer surface of the first copper layer of the single-sided composite. The temporary protective layer is an alkali-removable epoxy resin protective layer, and a deposition exposure window is retained in the corresponding area of the hole to improve the preferential deposition capability of the hole area.
[0123] Subsequently, plasma activation treatment was performed on the orifice and wall areas to improve the wettability of the inner surface of the orifice and the consistency of subsequent copper deposition. Using the first copper layer as the conductive basis for electrodeposition, the single-sided composite was placed in a copper sulfate-sulfuric acid electroplating solution for hole-filling electroplating. The concentration of copper sulfate was 180 g / L, the concentration of sulfuric acid was 60 g / L, the temperature of the electroplating solution was 22°C, and the current density was 6 A / dm³. 2 The electroplating time is 40 seconds.
[0124] During the electroplating process, copper is gradually deposited and grown from the end of the hole that contacts the first copper layer into the hole, forming a copper-conducting connection extending along the thickness direction of the polyethylene film. One end of the copper-conducting connection forms a stable electrical contact with the first copper layer, while the other end reaches or approaches the opening at the other end of the hole, so as to form an electrical contact with the second copper layer during subsequent lamination.
[0125] (4) Formation and composite of the second copper layer
[0126] A second copper layer with a thickness of approximately 1.0 μm is formed on the surface of the cathode roller using a copper sulfate-sulfuric acid electroplating solution with the same system as the first copper layer. The adhesive layer on the other side of the single-sided composite is then hot-pressed to the second copper layer at 80°C and 0.8 MPa for 5 seconds to form an electrical contact between the copper conductive connection and the second copper layer. After cooling, the composite is peeled off from the cathode roller to obtain a double-sided copper layer composite structure.
[0127] (5) Post-processing
[0128] The temporary protective layer was removed by treating the sample with 1.0 mol / L NaOH solution at 30°C for 20 min. The sample was then rinsed with deionized water until neutral and dried at 60°C to obtain the finished copper foil composite current collector.
[0129] The resulting product has the following structure: 1μm upper copper layer / 1μm upper adhesive layer / 2μm polyethylene film layer / 1μm lower adhesive layer / 1μm lower copper layer, with a total thickness of approximately 6μm.
[0130] The sample was tested and found to have a contact resistance of 2.08 mΩ between the upper and lower copper layers, a bending failure cycle count of 508, a tensile strength of 102 MPa, and a surface sheet resistance of 4.8 mΩ / □. The results indicate that, even with a relatively thin intermediate polymer film layer, the copper-filled edge hole conductive structure described in this invention can still produce an ultrathin copper foil composite current collector with stable conductivity between the upper and lower copper layers.
[0131] III. Performance Testing Methods, Test Results, and Comparative Analysis
[0132] To verify the comprehensive performance of the copper foil composite current collector of the present invention in terms of thickness control, conductivity between upper and lower copper layers, mechanical stability, and electrical conductivity, the samples obtained in Examples 1 to 3 were tested for thickness and thickness uniformity, contact resistance between upper and lower copper layers, bending durability, tensile properties, and in-plane conductivity. Unless otherwise stated, the test environment was 25±2℃ and 50±10% relative humidity.
[0133] Test method:
[0134] (1) Thickness and thickness uniformity test: A 100mm × 100mm sample was cut from the copper foil composite current collector obtained in the example. Ten measuring points were evenly selected on the sample surface, and the total thickness was measured using a high-precision thickness gauge. The average thickness was then calculated. The thickness uniformity deviation was calculated using the following formula:
[0135] Thickness uniformity deviation (%) = [(tmax - tmin) / tavg] × 100%
[0136] Where tmax is the maximum measured thickness, tmin is the minimum measured thickness, and tavg is the average thickness.
[0137] (2) Contact impedance test of upper and lower copper layers: Cut a sample with a size of 50mm×50mm, set test electrodes on the upper and lower surfaces of the sample in the edge area containing the copper conductive connection, and use a four-terminal micro-ohmmeter to measure the conduction impedance between the upper and lower copper layers. The contact pressure is controlled at 0.2MPa. Each sample is tested 5 times continuously, and the average value is taken as the test result.
[0138] (3) Bending durability test: A sample strip with a width of 15 mm and a length of 100 mm was cut and subjected to a 180° reciprocating bending test at room temperature. The bending radius was 2 mm, and one forward bend and one reverse bend were counted as one cycle. The bending frequency was 30 times / min. After every 100 cycles, the appearance of the sample and the conductivity of the upper and lower copper layers were checked. When obvious interlayer cracking, copper layer breakage, failure of copper conductive connection or interruption of conductivity occurred, it was judged as failure.
[0139] (4) Tensile property test: The specimens were cut according to the general method for tensile testing of film materials. The specimen width was 15 mm and the gauge length was 50 mm. The tensile test was carried out using an electronic tensile testing machine at a tensile speed of 50 mm / min. Five specimens were tested for each group of samples, and the average value was taken as the test result.
[0140] (5) In-plane conductivity test: The in-plane conductivity of the copper layer on the sample surface was tested using a four-probe tester. The test area was selected at the center of the sample and one point at a distance of 20 mm from the edge. A total of 5 points were tested for each sample, and the average value was taken. The in-plane conductivity is expressed as the surface sheet resistance, and the unit is mΩ / □.
[0141] The test results are summarized in Table 1 below.
[0142] Table 1 Summary of Performance Test Results of Copper Foil Composite Current Collectors in Examples 1 to 3
[0143] Test Project Example 1 Example 2 Example 3 Average total thickness / μm 9.0 11.6 6.0 Thickness uniformity deviation / % 4.2 3.8 4.7 Contact resistance of upper and lower copper layers / mΩ 1.86 1.94 2.08 Bending failure cycle count / times 523 612 508 Tensile strength / MPa 108 116 102 Surface sheet resistance (mΩ / □) 4.2 3.9 4.8
[0144] As shown in Table 1, the average total thickness of the samples in each embodiment is basically consistent with the design structure, and the thickness uniformity deviation is small. This indicates that the processes used in this invention, such as base film opening, adhesive coating, copper layer formation, hole filling electroplating, and hot pressing composite, have good thickness control capabilities and can meet the manufacturing requirements of ultra-thin copper foil composite current collectors.
[0145] Low milliohm-level contact impedances were measured between the upper and lower copper layers in all the embodiments, indicating that by setting a hole in the edge region of the intermediate polymer film layer and forming a conductive copper connection within the hole, a stable thickness-direction conductive path can be established between the upper and lower copper layers. Among them, the contact impedances of Examples 1 and 2 are both below 2.0 mΩ, while that of Example 3 is slightly higher, but still remains at a low level, indicating that the present invention still has good conductivity feasibility under relatively thin base film conditions.
[0146] The bending durability test results show that the samples of each embodiment can still maintain a long cycle life after multiple 180° reciprocating bends, indicating that the copper foil composite current collector of the present invention maintains good structural integrity and conductivity stability while maintaining the conductivity between the upper and lower copper layers. Among them, Example 2 has the highest number of bending failure cycles, indicating that appropriately increasing the structural thickness and optimizing the composite conditions helps to further improve the overall bending resistance. Although Example 3 is a thinner structure, it can still maintain a bending cycle life of more than 500 cycles, indicating that the present invention still has good mechanical adaptability under ultra-thin conditions.
[0147] The tensile test results show that the samples of each embodiment have good overall mechanical load-bearing capacity, which can meet the requirements of the current collector mechanical performance in subsequent battery manufacturing processes such as handling, coating, slitting and winding.
[0148] The in-plane conductivity test results show that the sheet resistance of the samples in each embodiment is at a low level, indicating that the formed copper layer has good continuity and density, which can meet the in-plane electron transport requirements as a battery current collector. At the same time, this also shows that the edge conduction structure set in this invention does not have a significant adverse effect on the in-plane conductivity of the main copper layer region.
[0149] As shown in Table 1, the present invention can effectively achieve thickness-direction conductivity between the upper and lower copper layers by setting holes in the edge region of the intermediate polymer film layer and filling the holes with copper to form a copper conductive connection. It also takes into account good thickness control capability, mechanical stability and in-plane conductivity, and is suitable for copper foil composite current collectors in electrochemical devices such as lithium batteries, sodium batteries and solid-state batteries.
Claims
1. A copper foil composite current collector, characterized in that, The device comprises, from top to bottom, an upper copper layer, an upper adhesive layer, an intermediate polymer film layer, a lower adhesive layer, and a lower copper layer. The edge region of the intermediate polymer film layer has at least one hole extending through its thickness direction. The hole is filled with copper to form a copper conductive connection. The copper conductive connection extends along the thickness direction of the intermediate polymer film layer, and its upper end is in electrical contact with the upper copper layer and its lower end is in electrical contact with the lower copper layer, so as to electrically connect the upper copper layer and the lower copper layer.
2. The copper foil composite current collector according to claim 1, characterized in that, The hole and the copper conductive connection are disposed in one edge region or two opposite edge regions of the intermediate polymer film layer.
3. The copper foil composite current collector according to claim 1, characterized in that, The hole can be a circular hole, an elliptical hole, a strip hole, or a polygonal hole.
4. The copper foil composite current collector according to claim 1, characterized in that, The aperture or characteristic size of the hole is 15μm-2000μm.
5. The copper foil composite current collector according to claim 1, characterized in that, The material of the intermediate polymer film layer is selected from one or more of polyethylene, polypropylene, polyethylene terephthalate, polyimide, polyvinylidene fluoride, and polytetrafluoroethylene.
6. The copper foil composite current collector according to claim 1, characterized in that, The upper adhesive layer and the lower adhesive layer each independently comprise one or more of maleic anhydride-grafted polyolefin adhesives, epoxy adhesives, acrylic adhesives, or polyurethane adhesives.
7. A method for preparing the copper foil composite current collector according to any one of claims 1 to 6, characterized in that, Includes the following steps: S1. Provide an intermediate polymer film layer, and form a hole extending through its thickness direction in the edge region of the intermediate polymer film layer; S2. An adhesive layer is provided on both sides of the intermediate polymer film layer; S3. A first copper layer is disposed on one side of the intermediate polymer film layer, so that the first copper layer is bonded to the adhesive layer on that side. S4. Fill the hole with copper to form a copper conductive connection portion that is in electrical contact with the first copper layer; S5. A second copper layer is provided on the other side of the intermediate polymer film layer, so that the second copper layer is in electrical contact with the copper conductive connection part, thereby making the first copper layer and the second copper layer electrically connected.
8. The preparation method according to claim 7, characterized in that, In step S1, the hole is formed by laser drilling, mechanical drilling, die cutting, or chemical etching.
9. The preparation method according to claim 7, characterized in that, In steps S3 and S5, the first copper layer and the second copper layer are respectively set in either of the following ways: prefabricated copper foil is hot-pressed and laminated with the corresponding adhesive layer; or a copper layer is first formed by electroplating and then laminated with the corresponding adhesive layer.
10. The preparation method according to claim 7, characterized in that, In step S4, the copper in the hole is formed by electroplating.
